Peningkatan Minat Beli Ulang melalui E-Service Quality: Studi Pada Konsumen Bukalapak - Setiawardani, Maya; Riyanto, Tri Agus (Jurnal Riset Bisnis dan Investasi, 2023)
The purpose of this study is to identify e-service quality that has been implemented by Bukalapak and the level of repurchase intention of its customers, as well as to reveal how much e-service quality can increase the repurchase intention of Bukalapak's consumers. The research method used is quantitative method, the sampling technique is using non-probability sampling with a purposive sampling approach of 176 respondents. Data collection was carried out through a questionnaire using a Likert scale. The data were processed using SPSS, using descriptive analysis, simple regression analysis, and hypothesis testing. The results of this study indicate that the level of e-service quality is in the high category, the level of consumer repurchase intention is in the sufficient category, and e-service quality can significantly increase consumer repurchase intention by 29.9%.